Analisis Niat menggunakan Self Service technology Berbasis Kebutuhan Dasar - Widyarini, Lydia Ari (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 1 Tahun 2021DO - 10.24843/MATRIK:JMBK.2021.v15.i01.p08, 2021)
In the context of technology developing in the society, Self-service technologies (SSTs) are becoming increasingly popular in retailing contexts, public service, banking, ticketing, parking, tourism, etc. Previous theories of SST adoption have largely ignored the basic human needs, such as competence, autonomy and relatedness that drive customer motivation and the use of SSTs in Indonesia. We address this theoretical gap and examine self-determination theory (SDT) to the Self Service Technology in general. Based on the argument proposed by SDT, self-determined motivation is hypothesized to mediate the relationships between autonomy, competence, and perceived anonymity, and the intention to use SSTs. Data collected from respondents form a structural equation model and support these hypotheses. This research shows that there is relation autonomy and competence to self determination and adoption intention to SSTs. There is no good relation anonymity to self determination and adoption intention to SSTs. There is relation Self Determination to adoption intention to SSTs. Self Determination mediate relationship of autonomy and competence on adoption intention, but Self Determination is not good mediation relationship of perceived anonymity on adoption intention to SSTs.